FRI0562 Association between joint regions with ultrasound-determined synovitis and systemic inflammatory markers. (12th June 2018) - Nakagomi, D.; Ikeda, K.; Kobayashi, K.; Hanai, S.; Yamagata, M.; Koh, R.; Furuta, S.; Nakajima, H.; Kitamura, K.
Abstract : Background: It is unknown which joint arthritis the inflammatory markers such as CRP or MMP-3 reflect. Objectives: We analysed the association between joint regions with ultrasound-determined synovitis and systemic inflammatory markers. Methods: We enrolled 152 patients with untreated arthritis and performed musculoskeletal ultrasound on 40 joints and determined a semiquantitative grade for power Doppler (PD) signals. We analysed the associations between PD scores in 8 joint regions and CRP/MMP-3 levels using multiple linear regression models with forced entry method. Results: Mean age was 55 years and 112 patients were female. Median CRP and MMP-3 were 0.36 mg/dl and 65.7 ng/ml. Median total PD score was 2. Standard regression coefficients for 8 joint regions were −0.009 for MCPs, 0.05 for PIPs, 0.372 for wrists, 0.183 for elbows, 0.628 for shoulders, 0.377 for knees, 0.261 for ankles, and −0.0131 for MTPs in a regression model to explain CRP using PD scores as dependent variables. Standard regression coefficients for the same joint regions were −5.134, –4.449, 24.061, 27.839, 22.508, 64.108, 36.501, and 2.539 to explain MMP-3. Conclusions: Systemic inflammatory markers such as CRP and MMP-3 do not accurately reflect the inflammation in small joints. Conversely, it is necessary to weight the large joints for the global ultrasound synovitis score to represent the severity of systemic inflammation. References: [1] Kawashiri SY, Kawakami A, Iwamoto N, et al. The power Doppler ultrasonography score from 24 synovial sites or 6 simplified synovial sites, including the metacarpophalangeal joints, reflects the clinical disease activity and level of serum biomarkers in patients with rheumatoid arthritis. Rheumatology (Oxford)2011May;50(5):962–5. [2] Gorai M, Ogasawara M, Matsuki Y, et al. Weighting with the Lansbury articular index improves the correlation of ultrasound score with serum matrix metalloproteinase-3 level in rheumatoid arthritis patients. Mod Rheumatol2014Nov;24(6):915–9. Disclosure of Interest: None declared